A Study On Processed Food Industry In Haryana - Rani, Manju; Singh, Dara (Journal of Neonatal Surgery, 2025)
Nearly 43% of India's land area is devoted to farming, making it one of the most agriculturally intensive economies in the world. Farming and related industries provide income for about two-thirds of the workforce. Investigating the processed food sector in Haryana is the focus of this article